ChemInform Abstract: A Diversified Approach to the Synthesis of Highly Functionalized Novel Azines and Azoles from 2H‐Pyran‐2‐ones. Issue 17 (4th April 2013) - Mishra, Pushyamitra; Kumar, Sandeep; Maurya, Hardesh K.; Gautam, Sanjay K.; Kumar, Brijesh; Tandon, Vishnu K.; Ram, Vishnu Ji
Abstract The highly facile, efficient, economically viable, and regioselective one‐pot procedure provides a new route for construction of functionalized pyrimidines, pyridines, and pyrazoles.